Developing English Supplementary Materials through Instructional Conversations - Nurhidayat, Eka; Rofi'i, Agus (Vision: Journal for Language and Foreign Language Learning, 2019)
This study aimed to develop English supplementary materials to meet the needs of nursing students on English learning through Instructional Conversation (IC) method. This research was categorized into research and development. The materials were validated by two experts to come to the final product. This research conducted at the Nursing Study Program involving students of the second semester. The data collected from classroom and checklist observation, questionnaire, an interview.Â  Considering the data collected, the English textbooks available and used in the Nursing Study Program contains English language learning materials that are still common and less specific for students used in the nursing study program. Therefore, English supplementary materials through Instructional Conversation (IC) method should be developed by considering the needs of lecturers and students. English supplementary materials through the Instructional Conversation method were developed by considering several aspects.